2002
DOI: 10.1290/1071-2690(2002)038<0365:faegfm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast and Epidermal Growth Factors Modulate Proliferation and Neural Cell Adhesion Molecule Expression in Epithelial Cells Derived From the Adult Mouse Tongue

Abstract: Lingual epithelial cells, including those of the taste buds, are regularly replaced by proliferative stem cells. We found that integrin beta(1), a keratinocyte stem cell marker, was expressed at the basal layer and taste buds of adult mouse tongue epithelium. We purified and cultured integrin beta(1)-positive cells (termed KT-1 cells), whose growth was stimulated by epidermal growth factor (EGF) and basic fibroblast growth factor (FGF-2). FGF-2 stimulation induced translocation of the FGF type I receptor (FGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Cell culture KT-1 cells were cultured and passaged as previously described with some modifications (Ookura et al 2002). Chelated fetal bovine serum was replaced with a cell-culture-grade bovine serum albumin (Proliant Biologicals, Ankeny, IA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture KT-1 cells were cultured and passaged as previously described with some modifications (Ookura et al 2002). Chelated fetal bovine serum was replaced with a cell-culture-grade bovine serum albumin (Proliant Biologicals, Ankeny, IA).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we isolated and cultured integrinb 1 -positive cells from mouse-tongue epithelium, and established cell line KT-1 (Ookura et al 2002). We found that EGF and FGF-2 stimulated proliferation of KT-1 cells and that calcium ion (1 mM) promoted multilayered cell differentiation, suggesting that this cell line is useful for analyzing the growth and differentiation of tongue epithelial cells.…”
Section: Introductionmentioning
confidence: 94%
“…The present study firstly reported an establishment of clonal cell lines from mouse taste buds. A lingual epithelial cell line (KT-1) was established from an adult mouse tongue (Ookura et al 2002) and used for analysis of regulation in growth and differentiation (Nakamura et al 2009). The line expressed NCAM, suggesting possible linage-linkage to taste cells.…”
Section: Pkd1l3mentioning
confidence: 99%
“…Cell lines are used to investigate growth and differentiation of lingual gustatory epithelial cells and taste transduction systems. Correlation between NCAM expression and FGF-2 stimulation in tongue epithelial cells was investigated using KT-1 cells established from mouse gustatory papillae (Ookura et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the small size of the oral cavity in mice and the limited amount of tissue available. However, one study has reported the development of a lingual epithelial cell line of mouse origin (KT-1 cells) (19). The KT-1 cells express markers consistent with a differentiation into gustatory epithelium rather than conventional oral epithelium.…”
Section: Introductionmentioning
confidence: 99%